2017
DOI: 10.1177/0276236617708740
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Influence of Self-Critical, Self-Managing, and Social-Assessing Self-Talk on Performance Outcomes in a Public Speaking Context

Abstract: This study examines how different types of self-talk (self-reinforcing, self-critical, self-managing, and social-assessing) influence speakers' emotional experience of public speaking anxiety and actual performance outcomes. A total of 152 participants reported their speech-specific self-talk frequencies and emotional states of anxiety at two time periods. External raters scored each participant's video-recorded speech. Results revealed that different types of self-talk exert influence on performance outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…We interpreted these results to suggest that individuals with high PSA were cognitively “busier” than those with low anxiety as they prepared for their upcoming speech. In a follow-up study (Shi et al., 2017), we found that self-managing self-talk was positively associated with the rated organization of an actual speech ( r = 0.23) and that PSA mediated the effects of self-critical and social-assessing self-talk on rated speech delivery, with self-critical self-talk indirectly decreasing speech delivery scores through its influence on increasing speakers’ PSA levels.…”
Section: The Cognitive Disruption Hypothesismentioning
confidence: 82%
“…We interpreted these results to suggest that individuals with high PSA were cognitively “busier” than those with low anxiety as they prepared for their upcoming speech. In a follow-up study (Shi et al., 2017), we found that self-managing self-talk was positively associated with the rated organization of an actual speech ( r = 0.23) and that PSA mediated the effects of self-critical and social-assessing self-talk on rated speech delivery, with self-critical self-talk indirectly decreasing speech delivery scores through its influence on increasing speakers’ PSA levels.…”
Section: The Cognitive Disruption Hypothesismentioning
confidence: 82%
“…To deal with anxiety, the technique of cognitive modification is the best because this technique specifically addresses negative discrepancy. An article published in this journal examines inner speech functions (e.g., Shi, Brinthaupt, & McCree, 2017). They examined self-talk before a speech in terms of self-managing self-talk (e.g., focuses on problem-solving thinking and selfregulation) and cited II research for alleviating stress and anxiety through the catharsis function (Choi et al, 2015).…”
Section: Public Speakingmentioning
confidence: 99%
“…Self-talk serves important cognitive and self-regulatory functions (e.g., Carver & Scheier, 1998; Morin, 2005; Winsler, Fernyhough, & Montero, 2009). A large research literature also highlights the role of self-talk in depression, anxiety, and other forms of dysfunction (e.g., Kendall, Howard, & Hays, 1989; Shi, Brinthaupt, & McCree, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(2009, Study 5) showed that frequent self-talkers reported higher levels of obsessive-compulsive tendencies (i.e., checking behaviors and impaired control over mental activities) compared to infrequent self-talkers. Shi et al. (2017) found that self-critical and social-assessing self-talk increased the anxiety levels of public speakers and hurt their actual speech performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation